Kidney cystosis in tuberous sclerosis in infants - E. F. Andreeva (Rossijskij Vestnik Perinatologii i Pediatrii, 2018)
The tuberous sclerosis is a systemic orphan disease. According to the literature data, the article summarizes the clinical and genetic features, presents the large and small criteria for the tuberous sclerosis diagnostics in children. The authors provide the comprehensive description of the kidney pathological condition specific for the tuberous sclerosis, which complicates considerably the course and determines the disease prognosis. The clinical observation of two tuberous sclerosis cases in the infants with very early detection of the polycystic kidney disease, quick growth of the kidney cysts and increase of the kidney volume, with formation of the nephrogenic arterial hypertension is presented. The TSC2/PKD1 syndrome (“adjacent gene syndrome”), which is a consequence of the simultaneous mutation of the adjacent genes on the short arm of chromosome 16, is the most probable in both cases.